Rutin-Loaded Nanocapsules Mitigate Vancomycin-Induced Hepatotoxicity: Development, Characterization, Optimization, and In Vivo Evaluation - Mohamed Ibrahim; Mohamed Fouad Mansour; Mahran Mohamed Abd El-Emam; Tarek khamis; Maha S. Kilany; Amira Ebrahim Alsemeh; Asmaa Monir Eltaweel; Milad Reda Qelliny; Mahmoud Mostafa; Marwa Mohamed El Sayed (Journal of Pharmaceutical Innovation, 2025)
Background Vancomycin (VCM)-induced hepatotoxicity is a significant clinical concern due to its association with oxidative stress, apoptosis, and inflammatory responses. This study investigated the formulation and potential preclinical application of rutin-loaded nanocapsules (RUT-NC) as a hepatoprotective agent against VCM-induced liver injury. Methods Hepatotoxicity was induced in rats through VCM administration, followed by oral treatment with RUT-NC. Liver function, oxidative stress markers, apoptotic proteins, lipid metabolism regulators, and inflammatory cytokines were subsequently evaluated. Results RUT-NC treatment significantly improved liver function parameters, attenuated oxidative stress, and modulated apoptotic pathways by downregulating the expression of p38 , p53 , caspase-8 , miR-122 , miR-7 , and beclin-1. Furthermore, RUT-NC restored lipid metabolism homeostasis by regulating the expression of PPAR-α, FASN, and SREBP-1. Notably, it exerted potent anti-inflammatory effects by suppressing NF-κB , TNF-α , IL-1β , IL-6 , IL-17 , and Gasdermin-D , thereby mitigating chronic liver inflammation. The pathological effects of VCM administration on hepatocytes were effectively counteracted by RUT-NC. Conclusion RUT-NC demonstrates promising hepatoprotective properties by enhancing antioxidant defenses, inhibiting apoptosis, regulating lipid metabolism, and reducing inflammation. These findings highlight its potential as a therapeutic intervention for drug-induced liver injury (DILI) and warrant further investigation for clinical application.